Řízení průběhu zakázky podnikem - Ocelíková, Klára (Vysoké učení technické v Brně. Fakulta podnikatelská, 2012)
Bakalářská práce se zabývá řízením průběhu zakázky podnikem, který obchoduje s různými druhy pneumatik. Stěžejní část práce je věnována určení problémů, které vznikají při realizaci zakázek a způsobují snižování zisku. Popis těchto problémů je obsažen v rozboru průběhu konkrétní zakázky. Práce obsahuje návrhy efektivnějšího řešení průběhu zakázek, řešení vzniklých problémů a návrhy změn vedoucí k zlepšení hospodárnosti a větší efektivnosti podnikových procesů. Tyto návrhy se týkají nejen samotného průběhu zakázek, ale také celkového fungování podniku. Práce obsahuje také vyčíslení přínosů navrhnutých řešení.

This thesis deals with order management process in a company that deals with different types of tyres. The main part of the thesis is dedicated to determination of issues that arise during processing of orders and cause reduction of the profit. Description of these issues is included in the analysis of a specific order. The thesis includes proposals for improvements of the procurement, a solution for arising problems and proposals for changes leading to better economic efficiency and more efficient business processes. These suggestions are not only related to the sole execution of the orders, but also to the overall performance of the company. The thesis contains also an economic quantification of the benefits of proposed solutions.
Order Management in the Company
Keywords: Zakázka; obchod; průběh zakázky; komunikace; dokumentace; logistika; outsourcing; cash flow; zásoby; likvidita; pneumatiky; Order; trade; order management; communication; documentation; logistics; outsourcing; cash flow; inventories; liquidity; tyres